The history of the Galician Division of the Waffen-SS. Volume 1. On the Eastern Front : April 1943 to July 1944 / Michael James Melnik - Melnyk, Michael James (The history of the Galician Division of the Waffen-SS, 2016)
"The History of the Galician Division of the Waffen SS: Volume One: On the Eastern Front, April 1943 to July 1944 is the first volume of a two part set on the history of the Galician Division based on twenty-five years research by historian Michael James Melnyk. The author has sourced additional new and hitherto unseen original material on all aspects of the Divisions history from archives and private collections in Europe, Australia, North American and Canada. Complemented by individual accounts and contributions of many veterans, which add an engaging personal dimension, this definitive account is lavishly illustrated with many unique photos and crammed full of details, notes and references." -- Publisher's description